Effect of Sewage Sludge on Nitrification Rate and Corn Nitrogen Uptake - Sorush Salek Gilani; Farshid Nourbakhsh; Yahya Rezainejad; Majid Afyuni (آب و فاضلاب, 2005)
Land application of sludge is a primary means of disposing municipal and industrial sewage sludge. The objectives of this research were to determine the effect of cumulative and residual sludge application on nitrogen (N) mineralization and nitrification and corn N uptake in a sludge amended clay loam soil (fine loamy, mixed thermic Typic Haplarigid). Soil samples from 0-15 cm depth were collected in a field that had received sewage sludge once, twice or three times during 1999-2001 at 0, 25, 50, and 100 mg ha-1. Rates of nitrification and N mineralization were determined in incubated soil samples. Corn N uptake was also measured. The results showed that sewage sludge application significantly increased soil organic carbon, N mineralization and nitrification. Also, corn yield and N-uptake increased significantly with sludge rates and number of times of sludge application. Regression analysis indicated significant correlations between soil organic C  and rate of nitrification (r= 0.825, P